Co-operation as a means of improving the condition of the working classes - Haughton, James (Statistical and Social Inquiry Society of Ireland, 1867)
I apprehend it will be admitted by all our members that few other subjects than the one which I have chosen are more important in their nature, or more in accordance with the purposes for which our Association was founded. An improvement in the condition of our working classes claims a prominent place in our discussions; and is a subject calculated, whenever it is brought under our notice, to call forth our warmest sympathies on behalf of a large number of our fellow men, from whose labor those who are in the possession of the comforts of life derive most of their means of enjoyment; while the producers of these comforts are themselves, in too many cases, subjected to great privations, from which, under the existing relations of society, they are, by their own unaided efforts, unable to free themselves. Many of these privations are no doubt caused by their own improvidence and intemperance. Perhaps such evils have always had to be borne by large numbers, in all countries, who depend for their subsistence on their daily labor; but they are not, on that account, the more endurable; nor is it, therefore, less the duty of the intelligent portions of the community, to strive by all legitimate means to establish a better and a happier state of social existence. Whether or not the co-operative system, which, not many years since, took hold on- the minds of some of the more intelligent of the working men in the United Kingdom, and which has more recently engaged the attention, and gained the active support, of some capitalists in England, be a wise means for effecting this worthy and desirable object, is now upon trial; and it is the subject to which I am desirous of drawing the attention of the members of this Society.
Read, 22nd January, 1866
Keywords: Co-operatives; Social improvement; 314.15